Characterization of the two component regulatory system PhoPR in Mycobacterium bovis - Garcia, Elizabeth Andrea (2018)
Mycobacterium bovis is the causative agent of bovine tuberculosis and is a member of Mycobacterium tuberculosis complex, which causes tuberculosis in a number of mammals including humans. Previous studies have shown that the genes encoding the two-component system PhoPR, which regulates several genes involved in the virulence of M. tuberculosis, are polymorphic in M. bovis, when compared to M. tuberculosis, which results in a dysfunctional two-component system. In this study we investigated the role of PhoPR in two M. bovis strains with differing degrees of virulence. We found that the deletion of phoP in an M. bovis isolate reduced its capacity of inducing phagosomal arrest in bovine macrophages. By gene expression analysis, we demonstrated that, in both M. bovis strains, PhoP regulates the expression of a putative lipid desaturase Mb1404-Mb1405, a protein involved in redox stress AhpC, the sulfolipid transporter Mmpl8 and the secreted antigen ESAT-6. Furthermore, the lack of PhoP increased the sensitivity to acidic stress and alteration of the biofilm/pellicle formation of M. bovis. Both these phenotypes are connected to bacterial redox homeostasis. Therefore, the results of this study suggest a role of PhoPR in M. bovis to be linked to the mechanisms that mycobacteria display to maintain their redox balance.